Pengembangan E-Modul Zat Aditif dan Adiktif Berbasis Etnosains untuk Meningkatkan Kreativitas Ilmiah Siswa SMP - Afina Aninnas; Bambang Subali; Arif Widiyatmoko (Postgraduate, University of Mataram, 2023)
This research aims to produce an ethnoscience-based e-module that is feasible and effective for increasing junior high school students' scientific creativity. This research method is development research or R&D (Research and Development) with the ADDIE model. The product trial design consists of a small-scale trial on 9 students and a large-scale trial by carrying out experimental research on 29 students. The data collection instruments used were an e-module feasibility analysis scale by experts and a scientific creativity essay test. The data analysis techniques used are percentage of feasibility, N-Gain test, and t test with a significance of <0.05. Based on the research, the results obtained show that the ethnoscience-based e-module on additives and addictive substances is feasible and effective for use and is able to increase students' scientific creativity in the high improvement category. There were differences between trials in class groups that used ethnoscience-based e-modules and class groups without treatment. The conclusion of this research is that the results of the development of an ethnoscience-based e-module regarding additives and addictive substances are able to increase the scientific creativity of junior high school students